Achieving Rich and Active Alkaline Hydrogen Evolution Heterostructures via Interface Engineering on 2D 1T‐MoS2 Quantum Sheets. (29th April 2020) - Chen, Wenshu; Gu, Jiajun; Du, Yongping; Song, Fang; Bu, Fanxing; Li, Jinghan; Yuan, Yang; Luo, Ruichun; Liu, Qinglei; Zhang, Di
Abstract: Large‐scale production of hydrogen from water‐alkali electrolyzers is impeded by the sluggish kinetics of hydrogen evolution reaction (HER) electrocatalysts. The hybridization of an acid‐active HER catalyst with a cocatalyst at the nanoscale helps boost HER kinetics in alkaline media. Here, it is demonstrated that 1T–MoS2 nanosheet edges (instead of basal planes) decorated by metal hydroxides form highly active edge 1T‐MoS 2 / edge Ni ( OH ) 2 heterostructures, which significantly enhance HER performance in alkaline media. Featured with rich edge 1T‐MoS 2 / edge Ni ( OH ) 2 sites, the fabricated 1T–MoS2 QS/Ni(OH)2 hybrid (quantum sized 1T–MoS2 sheets decorated with Ni(OH)2 via interface engineering) only requires overpotentials of 57 and 112 mV to drive HER current densities of 10 and 100 mA cm −2, respectively, and has a low Tafel slope of 30 mV dec −1 in 1 m KOH. So far, this is the best performance for MoS2 ‐based electrocatalysts and the 1T–MoS2 QS/Ni(OH)2 hybrid is among the best‐performing non‐Pt alkaline HER electrocatalysts known. The HER process is durable for 100 h at current densities up to 500 mA cm −2 . This work not only provides an active, cost‐effective, and robust alkaline HER electrocatalyst, but also demonstrates a design strategy for preparing high‐performance catalysts based on edge‐rich 2D quantum sheets for other catalytic reactions. Abstract : Edge 1T‐MoS 2 / edge Ni ( OH ) 2 heterostructures are highly active toward alkaline hydrogen evolution reaction (HER). The prepared 1T–MoS2 quantum sheet/Ni(OH)2 catalyst with rich edge 1T‐MoS 2 / edge Ni ( OH ) 2 sites efficiently dissociates H2 O to produce H2 in alkaline media in a bi‐functional manner, delivering excellent alkaline HER activity and stability surpassing that of Pt/C at high HER current densities (up to 500 mA cm −2 ).